In Vitro Activity of Auranofin in Combination With Aztreonam-Avibactam Against Metallo-β-lactamase (MBL)-Producing Enterobacterales - Wang, Wen; Huang, Shifeng; Zou, Chunhong; Ding, Yanhui; Wang, Huijuan; Pu, Shuli; Liao, Yunfeng; Du, Hong; Wang, Deqiang; Chen, Liang; Niu, Siqiang (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives To assess the efficacy of aztreonam-avibactam-auranofin (ATM-AVI-AUR) against a collection of 88 carbapenemase-producing Enterobacterales (CPE) clinical isolates and 6 in vitro selected ATM-AVI-resistant CPE with CMY-16 Tyr150Ser and Asn346His mutants or transformants. Methods MICs of imipenem, ceftazidime-avibact8am (CAZ-AVI), ATM-AVI, CAZ-AVI-AUR and ATM-AVI-AUR were determined via the broth microdilution method. Genetic background and carbapenemase genes were determined by PCR and Sanger sequencing. Results AUR alone showed little antibacterial activity with AUR MICs were greater than 64 μg/mL for all the 88 clinical CPE isolates. The addition of AUR (16 μg/mL) resulted in an 3-folding dilutions MIC reduction of ATM-AVI MIC50 (0.5 to 0.0625 μg/mL) and a 2-folding dilutions MIC reduction of MIC90 (1 to 0.25 μg/mL) against all 88 clinical CPE isolates, respectively. Notably, the reduced ATM-AVI MIC values were mainly found in MBL-producers, and the MIC50 and MIC90 reduced by 2-folding dilutions (0.25 to 0.0625 μg/mL) and 3-folding dilutions (2 to 0.25 μg/mL) respectively by AUR among the 51 MBL-producers. By contrast, the addition of AUR did not showed significant effects on ATM-AVI MIC50 (0.0625 μg/mL) and MIC90 (0.125 μg/mL) among single KPC-producers. Interestingly, the addition of AUR restored the ATM-AVI susceptibility against the 6 in vitro selected ATM-AVI-resistant CMY-16 Tyr150Ser and Asn346His mutants or transfromants, with the MICs reduced from ≥32 μg/mL (32->256 μg/mL) to ≤8 μg/mL (0.0625-8 μg/mL). Conclusions Our results demonstrated that AUR potentiated the activities of CAZ-AVI and ATM-AVI against MBL-producing isolates in vitro. Importantly, AUR restored the ATM-AVI activity against ATM-AVI resistant mutant strains. As a clinically approved drug, AUR might be repurposed in combination with ATM-AVI to treat infections caused by highly resistant MBL-producing Enterobacterales.